Changing the paradigm: Using strategic communications to promote recognition of child sexual abuse as a preventable public health problem. (July 2021) - Fix, Rebecca L.; Busso, Daniel S.; Mendelson, Tamar; Letourneau, Elizabeth J.
Abstract: Child sexual abuse (CSA) is common, severe, and substantively contributes to the global burden of disease through its impact on physical, mental, and behavioral health problems. While CSA is preventable through non-justice system response efforts, the vast majority of resources support criminal justice efforts to identify, prosecute, punish and monitor offenders after CSA has already occurred. Policy makers have not supported CSA prevention efforts in part because the public does not view CSA as a preventable public health problem. Here, we describe a program of research to be conducted to bridge the gaps between expert and public opinion about CSA as a preventable public health problem. We propose such research use a three-step approach to alter the way experts communicate about CSA to increase audiences' understanding of CSA as preventable. The three steps are: 1) identify consensus expert and public perspectives about CSA and the differences between these perspectives; 2) develop and test communication strategies to align public with expert perspectives; and 3) broadly disseminate validated communication strategies. Through this approach, we seek to develop and disseminate an informed communications strategy that effectively and accurately translates the science of CSA prevention to the public and the media.